Reducing the demand for available phosphorus in diets with added phytase for 8-to-21-day-old male broilers - Parra , John Armando; Teixeira , Luiz Fernando; Rostagno, Horacio Santiago; Hannas, Melissa Izabel (Spei Domus, 2015)
Introduction: in formulating concentrates for broilers (fe), inorganic sources of phosphorus (P) are used. Phytic P (derived from vegetables in concentrates) and excess added inorganic P are eliminated in the stool and cause problems to the environment. The aim of this study was to evaluate the reduction of the demand for available phosphorus (Pd) in 8-to-21-day-old male fe subject to three levels of Pd with phytase (500 FTU kg -1 of concentrate) on performance and bone parameters. Materials and methods: 480 Cobb® fe were used and distributed according to a completely randomized design. Pd levels were 0.391% (level of demand for male fe with medium performance) plus two levels: -10 % and +10%. The ratio between calcium and Pd was 2.13:1 (Ca:Pd). 8 replications of 20 birds per box were performed and an iso-nutrient diet was provided. Final weight, weight gain, concentrate intake, feed conversion, and ash, P and Ca contents in tibias were evaluated. Collected data were submitted to anova ; where there was a significant difference (P< 0.05), the treatment averages were compared by the snk test. Results:concentrate intake decreased (P=0.0265) at the level of 110%. As for bone mineralization, the 90% level resulted in lower ash (%), calcium (% e g) and P (% e g; P